Complete recovery in Wernicke's encephalopathy complicating hyperemesis gravidarum. Issue 2 (7th February 2019) - Aneja, Tripti; Chaturvedula, Latha; Nair, Pradeep Pankajakshan; Barathi, Deepak; Keepanasseril, Anish
Abstract : Wernicke's encephalopathy (WE) is an uncommon neurological complication in pregnancies complicated with hyperemesis due to thiamine deficiency. In women with hyperemesis, inadvertent glucose administration prior to thiamine supplementation triggers the development of neurological manifestations. Delay in the diagnosis can lead to maternal morbidity, and in one-third of cases may lead to persistence of some neurological deficit. With early recognition and thiamine supplementation, complete recovery is reported. We report a case of WE complicating a case of triplet pregnancy with hyperemesis gravidarum, which highlights the importance of early recognition and treatment, resulting in complete recovery as in the index case.